2010
DOI: 10.1037/a0017549
|View full text |Cite
|
Sign up to set email alerts
|

The effect of attention training on a behavioral test of contamination fears in individuals with subclinical obsessive-compulsive symptoms.

Abstract: In the current study, we evaluated the effectiveness of attention training in individuals with subclinical obsessive-compulsive symptoms. We hypothesized that after completing attention training, participants would be more likely to complete steps in a hierarchy approaching their feared contaminant compared to participants in the control condition. Participants completed a probe detection task by identifying letters replacing one member of a pair of words (neutral or contamination-related). We trained attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 39 publications
6
76
0
4
Order By: Relevance
“…For example, Clarke, Chen, and Guastella (2012) demonstrated that plasticity in attentional bias, defined as change in bias within a single session of ABM training, was predictive of treatment response to subsequent CBT, while attentional bias at a static time point was not. Moreover, Najmi and Amir (2010) found that plasticity in attentional bias within a single session of attention training mediated the effect of ABM training on behavioral approach toward feared objects in individuals with obsessive-compulsive symptoms. Thus, the extent to which attentional bias changes within a single session or is trained during ABM may relate to treatment outcome.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Clarke, Chen, and Guastella (2012) demonstrated that plasticity in attentional bias, defined as change in bias within a single session of ABM training, was predictive of treatment response to subsequent CBT, while attentional bias at a static time point was not. Moreover, Najmi and Amir (2010) found that plasticity in attentional bias within a single session of attention training mediated the effect of ABM training on behavioral approach toward feared objects in individuals with obsessive-compulsive symptoms. Thus, the extent to which attentional bias changes within a single session or is trained during ABM may relate to treatment outcome.…”
mentioning
confidence: 95%
“…More specifically, the plasticity in attentional bias, rather than attentional bias in itself, may be implicated in the maintenance of anxiety symptoms. While some data suggests that plasticity of attentional bias mediates outcome for a single session of ABM (Najmi & Amir, 2010), to date no studies have examined whether change in plasticity over a multi-session of ABM treatment protocol mediates the effect on symptom reductions. To examine effects of static versus plastic attentional bias, we report the results of both (a) static attentional bias at pre-treatment and change in static bias from pre- to post-treatment, and (b) plasticity of attentional bias during the first training session and change in this within-session plasticity of time, as moderating or mediating the treatment effects of ABM.…”
mentioning
confidence: 99%
“…ATT has been successfully utilized with a variety of anxious adult populations. Although ATT has most commonly been employed with socially anxious adults (e.g., Amir, Beard, Burns, & Bomyea, 2009;Klumpp & Amir, 2010;MacLeod & Bridle, 2006;Schmidt, Richey, Buckner, & Timpano, 2009), it has also been used to treat individuals with generalized anxiety disorder , pathological worry (Hazen, Vasey, & Schmidt, 2009), subclinical obsessive-compulsive disorder (OCD; Najmi & Amir, 2010), high trait levels of anxiety (Rutherford, MacLeod, & Campbell, 2004), and those undergoing stressful life events (MacLeod & Bridle, 2006).…”
mentioning
confidence: 98%
“…This could then be thought to subsequently improve performance of individuals with TA. CBM-A has shown to significantly reduce negative attention bias and subsequently levels of anxiety in obsessive compulsive symptoms (Najmi & Amir, 2010), generalised anxiety disorder (Hazen, Vasey, & Schmidt, 2009), separation anxiety disorder (Rozenman, Weersing, & Amir, 2011) and other anxiety-based conditions (MacLeod & Mathews, 2012, for a review) including worry (Hayes, Hirsch, & Mathews, 2010) and negative thought intrusion (Hirsch et al, 2011), which are cognitive components thought to be related to the detrimental effects of TA.…”
Section: Attentional Cognitive Bias Modificationmentioning
confidence: 99%